Pengaruh Eco-Friendly Packaging Terhadap Loyalitas Konsumen Pada Green Coffee Shop di Kota Bogor - Chaerudin, Mochamad Chaidar; Sulaiman, Anwar; Pramesti, Anindya Indah Ajeng; Gustiono, Azis Khairil; Ilvanny, Balqis Khalisafathinah; Firmansyah, Muhamad Faturhman; Apriliyanti, Putri Melati; Fathoningtyas, Tabitha Rahma (Sharia Journal and Education Center Publishing, 2026)
Growing environmental awareness has encouraged food and beverage businesses to implement sustainable business practices, including the adoption of eco-friendly packaging. This study aims to examine the effect of eco-friendly packaging on consumer loyalty at Green Coffee Shop Kopi Nako Daur Baur in Bogor City. A quantitative approach with a survey method was employed. Data were collected from 48 consumers selected through purposive sampling using structured questionnaires. The data were analyzed using validity tests, reliability tests, and simple linear regression analysis with statistical software. The findings reveal that eco-friendly packaging has a positive and significant impact on consumer loyalty. This indicates that environmentally friendly packaging can enhance consumers’ intentions to repurchase, recommend products, and maintain long-term commitment to the brand. The study concludes that eco-friendly packaging serves not only as an environmental initiative but also as an effective sustainable marketing strategy for strengthening consumer loyalty. These results provide practical implications for coffee shop businesses to integrate sustainability principles into product innovation and branding strategies.